The Impact of Growth Mindset Pedagogy on Listening Comprehension in Iranian EFL Learners - Arabi Zanjani , Seyed Behnam; Tasnimi, Mahshad; Azad, Mahnaz (Assessment and Practice in Educational Sciences, 2025)
This study aimed to examine whether instruction based on growth listening mindset principles significantly improves listening comprehension among Iranian EFL learners compared to traditional teaching approaches. A quasi-experimental design with a non-equivalent control group pretest–posttest was employed. The sample consisted of 144 Iranian EFL learners from Kish Khoban and Kish Mehr Institutes, randomly assigned to experimental (n = 72) and control (n = 72) groups. The experimental group received 16 sessions of growth mindset-based listening instruction, incorporating explicit and implicit training strategies that emphasized effort, resilience, and brain plasticity, while the control group underwent conventional listening instruction. Data were collected using the listening sections of IELTS 6 (pretest) and IELTS 8 (posttest), which were validated and reliable measures of listening comprehension. Statistical analyses included MANCOVA and two-way ANCOVA to evaluate the effects of growth mindset pedagogy, gender, and their interaction. Results showed a significant main effect of growth mindset pedagogy on listening comprehension (F = 28.43, p < .001, η² = .170), with the experimental group outperforming the control group on posttest scores. The main effect of gender was non-significant (F = 0.001, p = .993), but the interaction between gender and pedagogy was significant (F = 4.94, p = .028, η² = .034), indicating that while both males and females benefitted, female learners experienced slightly greater improvements in listening comprehension. The findings confirm that growth mindset pedagogy significantly enhances listening comprehension in Iranian EFL learners and is effective across genders, with stronger effects for females. The study underscores the potential of mindset-based interventions to foster resilience, motivation, and performance in receptive language skills, and highlights implications for EFL pedagogy, curriculum design, and teacher training.